Analyses of zoo-component expressions in German and Uzbek languages - Sapaeva Raykhon, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article highlights about the concepts of zoo –components while studying phraseological units .Also etymology of the words analysed and underpinned the peculiarities in the languages. Besides it antrocentric study of zoo-component expressions can be studied. Phraseological units are used in comparable languages ​​to give our speech more vividness, imagery, metaphor, stylistic coloring of expressiveness, and most importantly, relationships between people.